Contrast-enhanced ultrasound with VEGFR2-targeted microbubbles for monitoring combined anti-PD-L1/anti-CTLA-4 immunotherapy effects in a murine melanoma model with immunohistochemical validation - Felix L. Herr; Melissa J. Antons; Larissa V. Blume; Heidrun Hirner-Eppeneder; Sandra Kloiber-Langhorst; Amra Cimic; Jennifer Stueckl; Isabelle Tardy; Tanja Burkard; Jens Ricke; Wolfgang G. Kunz; Dirk-Andre Clevert; et al. (PLoS ONE, 2025)
Background Immune checkpoint inhibitors (ICIs) have emerged as a highly effective treatment option for patients with metastatic melanoma. As not all patients respond to ICI immunotherapy, imaging biomarkers are required to accurately monitor early response to therapy. Therefore, the aim of this study was to evaluate contrast-enhanced ultrasound (CEUS) with VEGFR2-targeted microbubbles for monitoring the effects of combined anti-PD-L1/anti-CTLA-4 immunotherapy in a murine melanoma model. Methods Murine melanoma allografts (B16-F10) were implanted subcutaneously in n = 10 therapy and n = 10 control female C57BL/6 mice. CEUS with VEGFR2-targeted microbubbles was performed on day 7 and 12. The therapy group received 3 intraperitoneal injections on days 7, 9, 11 of combined anti-PD-L1/anti-CTLA-4 immunotherapy, the control group received a placebo. CEUS assessed tumour perfusion during an early vascular phase (wash-in area under the curve = WiAUC) and VEGFR2-specific binding during a late molecular phase (signal intensity at 8 minutes (SI8min) and 10 minutes (SI10min)). For pathophysiological validation immunohistochemistry was performed. Results At follow-up, the CEUS perfusion parameter WiAUC demonstrated a significantly higher decrease in the therapy than in the control group (p = 0.021). At follow-up, the signal enhancement in the late phase was significantly lower in the therapy than in the control group (SI8min p = 0.003; SI10min p = 0.002). Immunohistochemistry revealed significantly more apoptotic tumour cells (p = 0.001), more tumour infiltrating lymphocytes (p = 0.049), lower tumour cell proliferation (p = 0.001), lower microvascular density (p = 0.003) and lower VEGFR2 expression (p = 0.003) in the therapy than in the control group. Conclusions CEUS with VEGFR2-targeted microbubbles allowed for monitoring early treatment effects of a combined anti-PD-L1/anti-CTLA-4 immunotherapy on melanoma allografts with significantly lower tumour perfusion and significantly lower binding of VEGFR2-targeted microbubbles in the therapy than in the control group.